Uncovering the mechanisms of salicylic acid-mediated abiotic stress tolerance in horticultural crops - Yang, Hua; Fang, Rui; Luo, Ling; Yang, Wei; Huang, Qiong; Yang, Chunlin; Hui, Wenkai; Gong, Wei; Wang, Jingyan (Frontiers in Plant Science, 2023)
Salicylic acid (SA) has been recognized as a promising molecule for improving abiotic stress tolerance in plants due to its ability to enhance antioxidant defense system, and promote root architecture system. Recent research has focused on uncovering the mechanisms by which SA confers abiotic stress tolerance in horticultural crops. SA has been shown to act as a signaling molecule that triggers various physiological and morphological responses in plants. SA regulates the production of reactive oxygen species (ROS). Moreover, it can also act as signaling molecule that regulate the expression of stress-responsive genes. SA can directly interact with various hormones, proteins and enzymes involved in abiotic stress tolerance. SA regulates the antioxidant enzymes activities that scavenge toxic ROS, thereby reducing oxidative damage in plants. SA can also activate protein kinases that phosphorylate and activate transcription factors involved in stress responses. Understanding these mechanisms is essential for developing effective strategies to improve crop resilience in the face of changing environmental conditions.Current information provides valuable insights for farmers and plant researchers, offering new strategies to enhance crop resilience and productivity in the face of environmental challenges. By harnessing the power of SA and its signaling pathways, farmers can develop more effective stress management techniques and optimize crop performance. Plant researchers can also explore innovative approaches to breed or engineer crops with enhanced stress tolerance, thereby contributing to sustainable agriculture and food security.